2009
DOI: 10.1007/s11269-009-9513-3
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Prospects of Sustainable Groundwater Management in the Indus Basin, Pakistan

Abstract: In Pakistan, on-demand availability of groundwater has transformed the concept of low and uncertain crop yields into more assured crop production. Increased crop yields has resulted in food security and improved rural livelihoods. However, this growth has also led to problems of overdraft, falling watertables and degradation of groundwater quality, and yields generally remain well below potential levels. Over the last three decades, Pakistan has tried several direct and indirect management strategies for groun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
144
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 254 publications
(159 citation statements)
references
References 12 publications
4
144
0
Order By: Relevance
“…This has improved the rural livelihood and the agricultural economy of Pakistan at large [10]. However, the increasing depth of the groundwater table has caused pumping costs to rise from 4.2 USD per 1000 m 3 for shallow tubewells (<15 m) to 12 USD per 1000 m 3 for deep tubewells (>15 m) [11]. The increased cost of pumping increases the cost of production, thereby decreasing the profit margins of farmers [12].…”
Section: Introductionmentioning
confidence: 99%
“…This has improved the rural livelihood and the agricultural economy of Pakistan at large [10]. However, the increasing depth of the groundwater table has caused pumping costs to rise from 4.2 USD per 1000 m 3 for shallow tubewells (<15 m) to 12 USD per 1000 m 3 for deep tubewells (>15 m) [11]. The increased cost of pumping increases the cost of production, thereby decreasing the profit margins of farmers [12].…”
Section: Introductionmentioning
confidence: 99%
“…Van Loon et al (2016) showed that humans are an important factor in the causes of droughts and the depletion of reservoirs. The depletion of reservoirs is mainly a result of groundwater pumping for drinking-water supply (Willis and Garrod 1998), irrigation (Amelung et al 1999;Foster et al 2004;Konikow and Kendy 2005;Hoque et al 2007;Qureshi et al 2010;Wada et al 2012) and industrial use (Hayashi et al 2009). Globally, groundwater withdrawal amounts to 750-800 km 3 year −1 and exceeds annual recharge in many places of the world (Shah et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The Indus Basin Irrigation System (IBIS) is the largest contiguous irrigation system in the world, providing water for more than 90 % of the food production in Pakistan, and around 21 % of the country's gross domestic product (Qureshi 2011;Ringler and Anwar 2013). Only around 40 % of total water demands can be met, and much of the deficit is supplied from groundwater, drawing on a major aquifer underlying the basin and closely linked to the river system (Ringler and Anwar 2013;Qureshi et al 2010). Both India and Pakistan generate significant hydropower from the Indus system.…”
Section: Description and Water Resource Issuesmentioning
confidence: 99%